Integral State: Critical Study on Land and Forest Management in the Post-May 2014 - Ongla, Olarn; Buddharaksa, Watcharabon (CMU Journal of Law and Social Sciences, 2019)
The land and natural resource management policies that have been implemented in Thailand have only served to strengthen the authority and control of the ruling classes.In order for these policies to allow for a more just rule of law, they would need to be acceptable to other social institutions. Following the 2014 military coup led by the National Council for Peace and Order, the forest and land policies have reflected a shift in power regarding at least two issues: (1) adjustment of control mechanisms and a new military-centric authority under the control of the Thailand National Security Council; and (2) a projection that State is the key protector and efficient provider of justice for their children’s natural resources.